1995
DOI: 10.1007/bf00713962
|View full text |Cite
|
Sign up to set email alerts
|

ZOO-FISH analysis: cat and human karyotypes closely resemble the putative ancestral mammalian karyotype

Abstract: DNA in situ hybridization with human chromosome specific DNA libraries was applied to compare the karyotypes of humans (Homo sapiens, 2n = 46) and cats (Felis catus, 2n = 38). For the autosomes alone, 30 segments of conserved synteny were revealed. The arrangement of these segments in the feline karyotype differs by only seven single chromosome breaks and one intrachromosomal inversion from their arrangement in humans. Comparison of these data with those recently obtained for pig and those available from conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
99
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(110 citation statements)
references
References 21 publications
10
99
0
1
Order By: Relevance
“…It somehow parallels the similarity of the karyotypes, which has been found to be close to the ancestral mammalian chromosome arrangement in both cases. 49 ( Figure 5d). Taken together, this points to high intron identity around alternatively included exons being a more general phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…It somehow parallels the similarity of the karyotypes, which has been found to be close to the ancestral mammalian chromosome arrangement in both cases. 49 ( Figure 5d). Taken together, this points to high intron identity around alternatively included exons being a more general phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…Todd (1970) suggested that the ancestral karyotype consisted of 14 chromosomes, whereas Matthey (1973) considered a chromosome number of 2n = 48 ‫ע‬ 8 as the ancestral eutherian condition. Still others favored an intermediate chromosome number like that of the cat (Rettenberger et al 1995b). If we analyze the additional information available through various chromosome painting studies hitherto carried out, the different hypotheses mentioned above can be tested, assuming that maximum parsimony should disclose the likely ancestral chromosomes/chromosomal complement.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of segment numbers detected in the different genomes by human CSLs range from 31 in cat and harbor seal (Rettenberger et al 1995b; to 53 in cattle (Hayes 1995). Variations in segment numbers detected for a particular species by different investigators (e.g., cattle ;Hayes 1995;Solinas-Toldo et al 1995;Chowdhary et al 1996) exclusively concern small segments and most likely reflect variation in complexity and origin of DNA probes applied by different laboratories (e.g., flow sorted or microdissected; see Yang et al 1997;Chaudhary et al 1998).…”
Section: Overall Conservation Of Karyotypic Organizationmentioning
confidence: 99%
See 2 more Smart Citations